Pengaruh Tingkat Pemahaman Peserta Didik terhadap Hasil Belajar Matematika pada Materi Lingkaran dalam Masa Pandemi Covid-19 - Nurul Ilmiyah; Candra Sari, Astrid; Dwi Febrianto, Reynaldi (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the effect of the level of understanding on the low learning outcomes of students during the Covid-19 pandemic at SMP Negeri 1 Rengel-Tuban on circle material. This research is a quantitative research with a sample of 31 students of class VIII E. The data collection technique in this study uses tests. The analytical method used by the researcher is the correlation technique and significance test. Correlation techniques are used to find the relationship between the level of understanding and student mathematics learning outcomes using a formula that has been determined by the researcher. Meanwhile, the significance test is used to prove whether the coefficient generated from the correlation formula can be applied to the population where the sample is taken. The results showed a correlation coefficient of 0.368. This means that there is a relationship between conceptual understanding and student mathematics learning outcomes, but the level of correlation is low. Meanwhile, from the results of the regression analysis to test the null hypothesis through the F test, it was found that the price of Fcount = 4.53 and the price of Ftable = 4.18. Because Fcount > Ftable, then H0 is rejected and H1 is accepted. This means that there is an influence between understanding the concept and the mathematics learning outcomes of students.